Tenurial security and agricultural investment: Evidence from Vietnam - Marc F. Bellemare; Kenn Chua; Julieth Santamaria; Khoa Vu (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2018)
In Vietnam, all lands belong to the state, who assigns usufruct rights to those lands to individuals and households. In 1993, the state gave 20-year usufruct rights to growers of annual crops, and 50-year usufruct rights to growers of perennial crops. In 2013, as the usufruct rights of growers of annual crops were set to expire, the Vietnamese government passed a law - the Land Law of 2013 - that extended the usufruct rights of all landowners by 50 years. We exploit this largely unanticipated shock to study the effect of the Land Law of 2013 on the investment behaviour of growers of annual crops. Using a difference-in-differences design, we find that the Land Law of 2013 is associated with a higher likelihood of investment in irrigation technology or soil and water conservation, but not other types of investment. Our results are robust to controlling for endogenous switching from annual to perennial crops, and our data support the parallel trends assumption. Our results also suggest that the long-term effects of the Land Law of 2013 are larger than its short-term effects.
Keywords: K11; O12; O13; Q15; 330; investment; land; land rights; Vietnam